Public space participative reactivation Case studies in Valencia and Madrid - Rosaura Ruiz Gallego (Culturas, 2017)
This work aims to understand the phenomenon of what we have propose to call "participatory reactivation of public space", which is characterized by the direct participation of citizens in the creation and management of social and cultural activities in public spaces, as part of a general will to reclaim that space as truly "public", where the citizens have power in the decision-making processes. This movement has been reinforced by the establishment of professional collectives and initiatives from public institutions.